2019
DOI: 10.1101/572362
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clades of huge phage from across Earth’s ecosystems

Abstract: Phage typically have small genomes and depend on their bacterial hosts for replication. DNA sequenced from many diverse ecosystems revealed hundreds of huge phage genomes, between 200 kbp and 716 kbp in length. Thirtyfour genomes were manually curated to completion, including the largest phage genomes yet reported. Expanded genetic repertoires include diverse and new CRISPRCas systems, tRNAs, tRNA synthetases, tRNA modification enzymes, translation initiation and elongation factors, and ribosomal proteins. Pha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…Little was known about the frequency of CRISPR-Cas in phages and plasmids, in spite of the previous studies describing their existence and relevance [16][17][18][19] . A recent preprint suggests that CRISPR-Cas may be particularly abundant in the phages of very large genomes 48 . Yet, we show that CRISPR-Cas are almost never carried by the phages available in the genome databases.…”
Section: Discussionmentioning
confidence: 99%
“…Little was known about the frequency of CRISPR-Cas in phages and plasmids, in spite of the previous studies describing their existence and relevance [16][17][18][19] . A recent preprint suggests that CRISPR-Cas may be particularly abundant in the phages of very large genomes 48 . Yet, we show that CRISPR-Cas are almost never carried by the phages available in the genome databases.…”
Section: Discussionmentioning
confidence: 99%
“…In the first case, 15 complete megaphage genomes, each > 540 kbp in length, were reconstructed and curated from human and animal microbiomes (Devoto et al 2019) . In the second case, 35 complete genomes > 200 kbp derived from phage, including the largest phage genomes yet reported (Al-Shayeb et al 2019) . The distinction of these sequences from prophage and the accurate size determinations could not be made without circularized genomes, and the complete, accurate inventory of genes would be precluded with only draft genomes.…”
Section: A Limited Number Of Published Complete Metagenome-assembled mentioning
confidence: 99%
“…Another seemingly rare error involves the artificial concatenation of an identical sequence, sometimes of hundreds of bp in length, repeated up to (or more than) three times. This has been a problem with some sequences of seemingly large phage deposited in public databases (as discussed by Devoto et al 2019 andAl-Shayeb, Sachdeva et al 2019). This phenomenon is easily identified by running a repeat finder, a step that should also be included in the curation to completion pipeline (see below).…”
Section: Genome Curation: Filling Scaffolding Gaps and Removal Of Locmentioning
confidence: 99%
“…Viruses are the most abundant biological entities in many ecosystems and can exert proportionately large effects on ecosystem functions (Fuhrman, 1999;Breitbart et al , 2002) . Viral MAGs have lead to the discovery of megaphages (with genomes >540 kb) from human and animal gut microbiomes , provided the first insights into the global distribution of such megaphages (Al-Shayeb et al , 2019) , and confirmed that environmental cyanophages contribute to global marine photosynthesis rates (Fridman et al , 2017) . However, the identification of viruses from metagenomes and their distinction from prophages continues to be challenging because there is not an established computational gold standard (Nooij et al , 2018) .…”
Section: Introductionmentioning
confidence: 92%